End-of-Life Care in Cardiovascular Disease - Goodlin, Sarah J.; Rich, Michael W.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2015)
Cardiovascular (CV) disease is the leading cause of death worldwide. While death rates from many acute CV illnesses have declined in developing countries, a substantial proportion of individuals with CV disease ultimately die from CV causes. As the population ages, the global burden of CV disease will continue to rise. Until recently, the focus of clinicians has been on saving lives and deferring death. Over the past decade there has  been growing recognition of the importance of palliative care and end of life care in CV disease.   While palliative and supportive care should be provided throughout the course of serious and life-shortening illnesses, this book focuses on issues that clinicians encounter in end-of-life care.  This book provides guidance to clinicians working across the breadth of care settings, in chronic progressive disease as well as sudden arrhythmic death andwith  advanced technologies. End-of-Life Care in Cardiovascular Disease is designed to assist clinicians, nurses, and other healthcare providers in addressing end of life care for patients with CV disease in a variety of common clinical scenarios.  Each chapter is written by expert clinicians and researchers, and concisely reviews current knowledge and recommendations for providing patient- and family-centered end-of-life care.
Introduction -- Dying from Cardiovascular Disease: An Epidemiologic Perspective -- Decision Making about End of Life Care: Advance Directives, Durable Power of Attorney for Healthcare, and Talking with Patients about Dying with Heart Disease -- Palliative Care and Hospice in Patients with Advanced Cardiovascular Disease -- End-of-Life Care in Hospitalized Patients with Cardiovascular and Cerebrovascular Disease -- End-of-Life Care in the Intensive Care Unit -- End-of-Life Care on the Surgical Services -- Management of Cardiovascular Death in the Emergency Department -- Management of Hospitalized Patients with Unexpected Cardiopulmonary Arrest -- End-of-Life Care in the Nursing Home -- End-of-Life Care in Patients with Congenital and Pediatric Heart Disease -- Psychosocial, Spiritual, and Existential Issues at End of Life -- Management of Implanted Cardiac Devices at End of Life -- Models of End-of-Life Care in the Home Environment.
Keywords: Cardiology; Geriatrics; Aging; Quality of life; Cardiology; Geriatrics/Gerontology.; Aging; Quality of Life Research